Marketing Strategy for Quail Eggs at Pesantren Manajer Tholabie, Malang, Indonesia - Marliana, Dina; Prafitri, Rizki; Winarto, Priyo Sugeng (Jurnal Ilmu-Ilmu Peternakan, 2024)
The marketing strategy research was conducted at Pesantren Manajer Tholabie, Baran Buring, Kedungkandang District, Malang City. The purpose of this study was to analyse the marketing strategy and marketing development strategy of quail egg products at this institution. The method involved a survey with a quantifiable approach. The data analysis in this study used Strengths, Weaknesses, Opportunities, Threats (SWOT) analysis. The results showed that the marketing strategy carried out by the Pesantren Manajer Tholabie Business Unit for promoting quail eggs was to use digital marketing in terms of WhatsApp blasts and conventional marketing, such as offering the product to the vegetable vendor and the neighbours of The Pesantren Manajer Tholabie. The strategy for developing quail egg marketing at the Pesantren Manajer Tholabie could be carried out using the S-O (Strenghts-Opportunities) strategy, such as improving business skills in agriculture, improving service to consumers, utilizing high market information access, maintaining good communication with consumers, utilizing the development and progress of science and technology for promotional activities and buying and selling products.